Características biométricas, fisiológicas e bioquímicas de pereiras europeias sobre diferentes porta-enxertos - Nedilha, Laís Cristina Bonato Malmann (2019)
The objective of this research was to evaluate the vegetative growth and the adaptability of cultivars of European pear trees grafted on different rootstocks, to the edaphoclimatic conditions of the Guarapuava region. The experiment was conducted at the Universidade Estadual do Centro-Oeste, in the years 2017 and 2018, in a randomized block design in a 2x3 factorial scheme, with four replications and five plants per experimental plot. The factors consisted of the combinations of the cultivars (Santa Maria and Rocha) with the rootstocks (OHF 69, OHF 87 and CAV 3), totaling six treatments. During the period from September 2017 to May 2018 (first period) and from May to November 2018 (second period), the following characteristics were evaluated: sprouting percentage, trunk diameter, plant height, number, diameter and length of branches, as well as the effects on chlorophyll a fluorescence, water potential, antioxidative enzyme activity and lipid peroxidation responses. The principal components analysis (PCA), together with the univariate analyzes (ANOVA and SNK), showed that the rootstock OHF 69 promoted the highest final sprouting rates for both cultivars, a higher percentage of trunk diameter growth and of plant height, when grafted under the cultivar Santa Maria. The rootstock CAV 3, followed by OHF 87, in both cultivars, showed less adaptability, due to the high activity of the antioxidative enzymes (superoxide dismutase, catalase and peroxidase), and consequently, higher lipid peroxidation, as well as lower concentration of pigments photosynthetic and low photosynthetic efficiency (PSII, (Y)). Based on the results obtained by PCA, which accounted for 90.3% (first evaluation period) and 91.5% (second evaluation period), the cultivar Rocha grafted on the rootstock OHF 69, followed by the combination Santa Maria / OHF 69, were the combinations that presented better compatibility and adaptability to the soil and climate conditions in the Guarapuava region, in the state of Paraná.